Reduced Turn-On Voltage and Boosted Mobility in Monolayer WS2 Transistors by Mild Ar+ Plasma Treatment - Hou, Junfeng; Ke, Congming; Chen, Jiajun; Sun, Baofan; Xia, Yuanzheng; Li, Xu; Chen, Ting; Wu, Yaping; Wu, Zhiming; Kang, Junyong (ACS applied materials & interfaces, 2020)
Monolayer two-dimensional transition-metal dichalcogenides, such as tungsten disulfide (WS2), are regarded as promising candidates for optoelectronic and electronic applications. Although theoretical calculations have predicted outstanding electronic properties of WS2, the performance of WS2-based electronic devices is still limited by the relatively high Schottky barrier and low carrier mobility. In this work, low-energy argon (Ar+) plasma treatment was used as a nondestructive preconditioning technique to tailor the electrical properties of the WS2 monolayer grown by chemical vapor deposition. Photoluminescence and Raman spectroscopy were used to monitor the modified optical properties of WS2 with increasing plasma treatment time. An improved electrical conductivity was observed after a short-time plasma treatment. The physical mechanism was further revealed by a comparative study between top-electrode and bottom-electrode devices and simulation based on the density functional theory. It is concluded that mild Ar+ plasma treatment can effectively lower the Schottky barrier height and the effective mass of carriers, which reduces the turn-on voltage and enhances the mobility, respectively. However, if the processing time is too long, the WS2 lattice structure will be destroyed. This work has provided an effective method for manipulating the Schottky barrier and mobility of monolayer WS2 transistors and paves the way for developing high-performance electronic devices based on 2D semiconductors.